2010
DOI: 10.1063/1.3517453
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on dielectric barrier discharge actuators operating in pulse mode

Abstract: An experimental investigation is performed on the operation of dielectric barrier discharge plasma actuators used as manipulators of secondary and unsteady flow structures such as boundary layer instabilities or shedding vortices. The actuators are tested mainly in pulse mode. High sample rate hot-wire measurements of the induced velocity field downstream of the actuator are taken for the cases of pulse actuation in still air as well as in a laminar boundary layer. Complementary voltage and current measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…We computed the development of the wall jet induced by the plasma actuator, and the magnitude of the maximum time-averaged wall jet was the same for all cases that we considered. Most of results are consistent with the observations reported for previous experiments Moreau, 2010, Kotsonis andVeldhuis, 2010), and this lends further support to our computed results. As an area of future work, we intend to investigate the characteristics of the flow induced by a plasma actuator with burst modulations in the free-stream.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We computed the development of the wall jet induced by the plasma actuator, and the magnitude of the maximum time-averaged wall jet was the same for all cases that we considered. Most of results are consistent with the observations reported for previous experiments Moreau, 2010, Kotsonis andVeldhuis, 2010), and this lends further support to our computed results. As an area of future work, we intend to investigate the characteristics of the flow induced by a plasma actuator with burst modulations in the free-stream.…”
Section: Discussionsupporting
confidence: 93%
“…Their results showed that burst modulation with a burst ratio (BR=t on f burst ) or duty cycle of 50% resulted in two frequency peaks, each of which is the result of superimposing numerous harmonics; for this case, the time-averaged velocity was low, and there were rapid fluctuations in the bust frequency ( f burst ), which was low. Kotsonis and Veldhuis (2010) used hot-wire probes to measure the total velocity induced by a single asymmetric plasma actuator with modulated bursts; V pp was 10,000 V, and f base was 2,000 Hz. Several combinations of f burst and BR were tested.…”
Section: Introductionmentioning
confidence: 99%
“…13(a) that increasing the duty cycle at a constant excitation frequency of 100Hz increases the required current and thus the induced velocity. The quasi-linear increase in current draw is in agreement with the results of Kotsonis and Veldhuis (2010) and Taleghani et al (2012) for duty cycles in the range of 15%-80%. However, excitation frequency at a constant duty cycle of 50% does not have a significant effect on the current draw ( Fig.…”
Section: Results and Discussion Non-stationary Actuationsupporting
confidence: 89%
“…Several excellent reviews are published on the topic, and here we only mention the most relevant from recent studies. Kotsonis and Veldhuis (2010) performed experiments to study the DBD actuators in pulse mode. They focused on the effectiveness of the actuator in inducing fluctuating velocity components.…”
Section: Introductionmentioning
confidence: 99%
“…Kotsonis 11 published a paper discussing the pulsating performance of individual actuators at frequencies from 25 to 400 Hz. His results were for the standard plasma actuator not opposing plasma actuators but the results should be similar.…”
Section: Plasma Actuatorsmentioning
confidence: 99%